Antecedents and consequences of perceived coolness for Generation Y in the context of creative tourism - A case study of the Pier 2 Art Center in Taiwan. (June 2019) - Chen, Ching-Fu; Chou, Shih-Huan
Abstract: This study investigates the role of perceived coolness in terms of creative tourism destination consumption and its antecedents as well as the consequences for Generation Y tourists. Specifically, we denote three antecedents of perceived coolness (uniqueness, identification, and attractiveness) and three consequences (satisfaction, place attachment, and destination loyalty) in the proposed creative tourism experience model. Results from a sample of 281 Generation Y tourists visiting a popular creative tourism site in Taiwan show that all three antecedents are positively related to perceived coolness, which in turn positively affects satisfaction and place attachment. In addition, both satisfaction and place attachment mediate the effect of perceived coolness on destination loyalty. Implications and suggestions for future research are also discussed. Highlights: Perceived coolness was introduced to represent tourist experience of creative tourism. Antecedents and consequences of perceived coolness were empirically investigated. Uniqueness, identification and attractiveness affect perceived coolness. Perceived coolness affects tourist satisfaction, place attachment and destination loyalty. Evidence from a sample of Taiwanese Generation Y tourists was presented.